Structural characterization and immunomodulatory activity of a novel polysaccharide from Ficus carica. Issue 7 (5th July 2018) - Du, Juan; Li, Jingjing; Zhu, Jianhua; Huang, Chunhua; Bi, Sixue; Song, Liyan; Hu, Xianjing; Yu, Rongmin
Abstract : A novel polysaccharide (FCPW80-2) with a molecular weight of 1.21 × 10 5 Da was first isolated from Ficus carica through hot water extraction and several chromatographic methods. Abstract : A novel polysaccharide (FCPW80-2) with a molecular weight of 1.21 × 10 5 Da was first isolated from Ficus carica through hot water extraction and several chromatographic methods. The structure of FCPW80-2 was determined by chemical and instrumental analysis. The results showed that the backbone of FCPW80-2 consists of (1→5)-linked α-l -Ara, (1→3, 6)-linked β-d -Man and (1→4, 6)-linked β-d -Gal. The branches of FCPW80-2 consist of (1→4)-linked α-d -Glc and (1→3)-linked β-l -Rha terminated with (1→)-linked β-d -Glc. In vitro immunomodulatory activity assays revealed that FCPW80-2 could markedly promote the secretion of cytotoxic molecules (NO) and cytokines (TNF-α and IL-6) as well as the phagocytosis of RAW264.7 macrophages. Moreover, TLR2 was found to be a pattern recognition receptor (PRR) of FCPW80-2, and its related mitogen-activated protein kinases (MAPKs), including p-ERK, p-JNK and p-p38, were rapidly upregulated by FCPW80-2 in RAW264.7 macrophages. Furthermore, FCPW80-2 could not only upregulate the expression of p-p65 and p-IκB-α, but also cause the translocation of nuclear factor-kappa B (NF-κB) p65 from cytosol to nuclei in RAW264.7 macrophages. The results demonstrated that MAPK and NF-κB signalling pathways participated in FCPW80-2-induced macrophage activation and FCPW80-2 could be developed as a potential immunomodulating functional food.